2020
DOI: 10.12775/eq.2020.013
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical and geospatial assessment of soil pollution with heavy metals in Pavlograd city (Ukraine)

Abstract: This paper presents the result of studies of the geostatistical and geospatial assessment heavy metal pollution in soils caused by various technogenic sources to assess the environmental impact of industrial agglomeration activitiy in the Pavlograd city. The main sources of technogenic pollution in the Pavlograd city and suburban areas are industrial enterprises, coal-fired plants, mine dumps and other. The vast number of analyzed soil samples with weakly acidic pH values from 6.3 to 6.8 is characterized as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…All territory investigated in these three directions can be used for cultivating agricultural crops, but strict sanitary control of the production is an indispensable prerequisite. The essence of this research is that in previous studies by a number of scientists (Kharytonov et al, 2008(Kharytonov et al, , 2016(Kharytonov et al, , 2020, the physiological features of sprouts of red radish roots showed the ability of seeds to respond to exogenous chemical influences during germination. This is primarily reflected in the difference in the length of the root sprouts, in particular, the decrease in biometric indicators in response to the increased negative impact.…”
Section: ℎе = − * 100mentioning
confidence: 97%
“…All territory investigated in these three directions can be used for cultivating agricultural crops, but strict sanitary control of the production is an indispensable prerequisite. The essence of this research is that in previous studies by a number of scientists (Kharytonov et al, 2008(Kharytonov et al, , 2016(Kharytonov et al, , 2020, the physiological features of sprouts of red radish roots showed the ability of seeds to respond to exogenous chemical influences during germination. This is primarily reflected in the difference in the length of the root sprouts, in particular, the decrease in biometric indicators in response to the increased negative impact.…”
Section: ℎе = − * 100mentioning
confidence: 97%
“…The few sewage treatment plants in the region are frequently overwhelmed, bypassing raw sewage to rivers and streams. Soil pollution in the Pavlograd area has led to significant declines in agricultural output and the withdrawal of agricultural land from circulation (Kharytonov et al, 2020). With respect to air quality, the World Health Organization ranks Ukraine as having the greatest air pollution and airborne health hazards in Europe (Pehchevski, 2020).…”
Section: Important Considerations For Us Nrda In Ukrainementioning
confidence: 99%
“…In many areas of Ukrainian territory, the content of Ni, Zn, and Co in the soil is at less than maximal permissible level (Sytar and Prasad, 2016). Research in 2020 by Czech and Ukrainian ecologists found increased levels of heavy metals in the rivers and soils of Pavlograd city, Dnipropetrovsk region (Kharytonov et al, 2020).…”
Section: The Monitoring Of Heavy Metal Pollution In Soil Inmentioning
confidence: 99%
“…Characteristics of main crop production areas under military conflict in Ukraine (2022) regarding their possible yield production and possible heavy metals contamination (State Statistics Service of Ukraine (2021),Sytar and Prasad (2016),Kharytonov et al (2020)) …”
mentioning
confidence: 99%